Getting started with Agile - Fascinari, Massimo (Packt Publishing, 2017)
"The Agile movement seeks alternatives to traditional project management. Agile approaches can help teams to respond to unpredictability through incremental, iterative work cadences and empirical feedback. The video course is divided into a number of sections that take you through the fundamental aspects of Agile development, progressing through each aspect at a pace that keeps you hooked. In the first section, you will learn how to create an Agile environment, and find out how to build and manage your backlog and Kanban board. Next, you’ll look into establishing correct roles in your team, and go through practical examples of product development planning and scrum organization. In the third section, you will learn how to plan an efficient product roadmap and schedule releases, and also work with the WSJF lean method and feedback process. Finally, you will discover how to manage your product using an end-to-end approach by making hypotheses and easily validate them. By the end of this video course, you’ll know how to make the best of the Agile methodology to plan, manage, and develop your team and product."--Resource description page.